Assédio moral no trabalho: significados elaborados por servidores de uma instituição pública de ensino superior - Souza, Anne Ludmilla Maul de (2019)
The purpose of this study is to describe the meanings of bullying at work, prepared by public servants of a federal institution of higher education. Ten employees, including technicians and active teachers of the Center of Education - CE and the Center for Human Sciences Letters and Arts – CCHLA and the Pro-Rector's Office - PRO of the institution under study participated, chosen because of the greater proximity of the researcher, who is also a servant, with those sectors. Sociodemographic questionnaires and semi-structured interviews were applied. The data were submitted to thematic content analysis with the help of the software ALCESTE, based on socio-historical-cultural perspective. The meanings of moral harassment in the work elaborated by civil servants of the public service were configured in three classes: Conception of Moral Work Harassment with 44.90% of the speeches; Confrontation: Awareness, Regulation, Investigation and Punishment with 32.65%; Relationship 'me and the other' with 22.45%. It is concluded that the meaning of bullying in the work elaborated by the interviewees makes evident the importance of the subject, which should be discussed and analyzed abundantly. In the academic and learning environment, it becomes even clearer that the people involved try to understand the consequences that the problem can cause in the individual's life as a worker as well as a student. The awareness and the resumption of their identity through the process of learning and praxis can promote the renewal and transformation of the subject and the organizational contexts in the face of the difficulties and suffering faced, linked to the incidence of bullying in the work environment. The aim of this study is to contribute to the production of knowledge about the subject, as well as to reflect on processes and practices in daily life in higher education institutions, presenting possible thematic axes for analysis and possibilities for intervention and inspiration of new studies.